Managerial competences and their management: a study in Brazilian inns of a historic city (Tiradentes, Minas Gerais) - Leandro Eduardo Vieira Barros; Kely César Martins de Paiva; Mônica Carvalho Alves Cappelle (Tourism & Management Studies)
Tourism has become prominent on the national scene, both for national authorities and society. In this environment, the hotels’ branch manager plays a key role in which managerial competences are required to manage the project and the provision of services. For this reason, the objective of this research was to identify and analyze the management competences of hotel managers in Tiradentes (Minas Gerais, Brazil). For that, a field research with descriptive, qualitative and quantitative approach was carried out. It was observed that inns are family-owned businesses with little training in the area and the main role of managers is to be a mentor, focusing on human relationships. The inns contribute to the management of competences process, which occurs mainly due to an individual’s daily action in the organization, also as with formal training incentives. Finally, we present the research limitations and suggestions for future research.